Insights into short- and long-term effects of loading nickel nanoparticles on anaerobic digestion with flocculent sludge. Issue 9 (29th July 2019) - He, Chuan-Shu; Ding, Rong-Rong; Wang, Yi-Ran; Li, Qi; Wang, Yi-Xuan; Mu, Yang
Abstract : Exposure to Ni-NPs induced a time- and dosage-dependent inhibition on all the steps of anaerobic digestion. Abstract : The insights into both short-term and long-term effects of Ni nanoparticles (Ni-NPs) on anaerobic digestion (AD) with anaerobic flocculent sludge (AFS) were explored in this study. Results showed that the presence of Ni-NPs induced an irreversible and dosage-dependent inhibition on the methanogenic activity of the AFS. Three steps of anaerobic digestion, including glucose acidification, acetification and methanation, were all suppressed in the presence of Ni-NPs at high dosages after short-term observation, while the acetoclastic methanation process was the most influenced. Extended exposure to a low level of Ni-NPs (1 mg per g-TSS, total suspended solids) stimulated their toxicity to acetoclastic methanogenic activity, and that to high dosages of Ni-NPs would enhance their ability to inhibit all the steps involved in the AD process. When the dosages of Ni-NPs were 50 and 200 mg per g-TSS, the estimated CH4 volume was respectively reduced by 11.8% to 91.1% and 18.6% to 96.3% of the control, and the estimated kinetic rate constant for CH4 generation decreased from 0.45 to 0.12 d −1 and 0.40 to 0.09 d −1, respectively, over long-term experiments. As the dosage of Ni-NPs was increased to 600 mg per g-TSS, almost no methane was generated from the second cycle. Depression of cell viability caused by released Ni 2+ through attacking biological molecules of the cell was speculated to be an important toxic mechanism. Microbial analysis results indicated that long-term exposure to Ni-NPs decreased the abundance of microbial communities of the AFS and the relative abundance of predominant archaeal genera mediating acetoclastic methanogenesis.